Androgen receptor footprint on the way to prostate cancer progression - Hodgson, Myles C. (Springer-Verlag, 2011)
The prostate gland is exquisitely sensitive to androgen receptor (AR) signaling. AR signaling is obligatory for prostate development and changes in AR levels, its ligands or shifts in AR mode of action are reflected in the physiology of the prostate. The AR is intimately linked to prostate cancer biology through the regulation of epithelial proliferation, suppression of apoptosis and the development of castration-resistant disease. Thus, AR is the primary therapeutic target in various prostate diseases such as BPH and cancer. Although some tumors lose AR expression, most retain the AR and have elevated levels and/or shifts in activity that are required for tumor progression and metastasis. New AR inhibitors currently in clinical trials with higher receptor affinity and specificity may improve prostate cancer patient outcome. Several events play an important role in initiation, primary tumor development and metastatic spread. Androgen receptor activity and promoter specificity change due to altered coregulator expression. Changes in epigenetic surveillance alter the AR cistrome. Both systemic and local inflammation increases with PCa progression affecting AR levels, activity, and requirement for ligand. Our current understanding of AR biology suggest that global androgen suppression may drive the development of castration-resistant disease and therefore the question remains: Does effective inhibition of AR activity mark the end of the road for PCa or only a sharp turn toward a different type of malignancy?